Peripheral venous thrombophlebitis risk and the role of hand washing - Neopane, A (Nepal Journal of Medical Sciences, 2013)
Background: Thrombophlebitis is an important complication of peripheral vein cannulation. Various factors are known to increase the risk of thrombophlebitis and have been studied by different authors. Regarding factors leading to risk reduction of thrombophlebitis aseptic measures taken during insertion has been an important factor. However handwashing and its role in reducing the incidence of thrombophlebitis have not been studied. The objective of this study was to find the risk reducing role of hand washing in incidence of thrombophlebitis. Methods: A prospective observational hospital based study was designed and conducted among patients admitted for intravenous medication or infusion and needed cannulation. They were followed and evaluated for various risk factors and onset of thrombophlebitis. Results expressed as relative risk and odds ratio. Results: Hand washing is the single most important risk reducing factor for development of peripheral vein thrombophlebitis in patients in whom peripheral vein cannulation is done. The odds ratio of developing thrombophlebitis in hand washing group was only 0.25 (95% CI .07-.82) and RR was 0.78 (95% CI.64-.94) with p=.017. Conclusion: Six step hand washing was the single most useful factor for reducing the risk of thrombophlebitis. Nepal Journal of Medical Sciences | Volume 02 | Number 01 | Jan-Jun 2013 | Page 26-29 DOI: http://dx.doi.org/10.3126/njms.v2i1.7647